Low power current sources for bioimpedance measurements: a comparison between Howland and OTA-based CMOS circuits - Bertemes-Filho Pedro; C. Vincence Volney; M. Santos Marcio; X. Zanatta Ilson (Journal of Electrical Bioimpedance, 2012)
Multifrequency Electrical Bioimpedance (MEB) has been widely used as a non-invasive technique for characterizing tissues. Most MEB systems use wideband current sources for injecting current and instrumentation amplifiers for measuring the resultant potential difference. To be viable current sources should have intrinsically high output impedance for a very wide frequency range. Most contemporary current sources in MEB systems are based on the Howland circuit. The objective of this work is to compare the Mirrored Modified Howland Current Source (MMHCS) with three Operational Transconductance Amplifier (OTA) based voltage controlled current sources (i.e., class-A, class-AB and current conveyor). The results show that both current conveyor and class-AB OTA-based current sources have a wider output current frequency response and an output impedance of 226% larger than the MMHCS circuit at 1 MHz. The presented class-AB OTA circuit has a power consumption of 4.6 mW whereas current conveyor consumed 1.6 mW. However, the MMHCS circuit had a maximum total harmonic distortion of 0.5% over the input voltage from -0.5 to +0.5 V. The OTA-based current sources are going to be integrated in a semiconductor process. The results might be useful for cell impedance measurements and for very low power bioimpedance applications.